First Report of Peach-Associated Luteovirus (PaLV) Infecting Almond Trees (Prunus dulcis) in Spain - Morán, Felix; Olmos, Antonio; malagón, Jose; Candresse, Thierry; Ruiz Garcia, Ana Belén (APS, 2025)
Peach-associated luteovirus (PaLV) belongs to the genus Luteovirus, family Tombusviridae. To date, PaLV has only been reported in peach (Prunus persica) and its presence detected in the Republic of Georgia (Wu et al. 2017), China (Zhou et al. 2018), and a range of European countries (Khalili et al. 2023). PaLV-infected peach plants have been reported to show pitting of the fruit surface (Sorrentino et al. 2018) or leaf yellowing and mosaic (Zhou et al. 2018). However, the association between PaLV and symptoms in peach remains very doubtful (Khalili et al. 2023). In October 2021, a plot of almond trees (cv. Lauranne) located in Valencia, Spain, was surveyed because of an outbreak of almond foamy canker, a syndrome of unknown etiology characterized by the presence of foam on the main trunk that leads to sudden tree death. Foliar and subcortical trunk tissue collected from both a symptomatic (IVIA_12111S) and an asymptomatic (IVIA_12111A) tree was analyzed by high-throughput sequencing. Total RNA extracted from each sample was individually sequenced using TruSeq Ribo-Zero Illumina technology on a Novaseq 6000 platform. Bioinformatic analysis (CLC Genomics Workbench version 10.1.1) generated 9,175 and 5,039 de novo contigs, respectively. Interestingly, BLASTX analysis of the asymptomatic plant dataset revealed a contig of 5,820 nt (covered by 5,297 out of 1,251,368 reads), representing a near complete PaLV genome. The sequence of this isolate PaLV-12111A (GenBank accession no. PQ660174) shares highest nucleotide (nt) identity (97.1%) with a peach isolate from Spain (IVIM18, KY635989.1). The presence of PaLV in this almond tree was confirmed by RT-PCR using PaLV-specific primers (Sorrentino et al. 2018) followed by amplicon Sanger sequencing. Moreover, the RT-PCR analysis of 27 additional trees from the same plot showed the presence of two additional PaLV-infected almonds, which were also asymptomatic. These results identify almond as a new natural host of PaLV, which confirms the otherwise unpublished existence in GenBank of a PaLV genomic sequence from Iran reportedly from almond (ON192959). In order to further confirm the presence of PaLV in almond, two publicly available Sequence Read Archives independently generated in Spain but also involving the Lauranne variety (ERR8601621 and ERR8601618) were datamined, allowing the recovery of two additional near-complete PaLV genomes sharing 99.68% nt identity and showing 95.6% nt identity with PaLV-12111A. The phylogenetic analysis of available PaLV genomes revealed that both almond and peach Spanish PaLV isolates grouped together in a cluster genetically distant from the Iranian almond isolate. These results suggest phylogenetic relationships associated with geography rather than host adaptation. Interestingly, the presence of PaLV in Spain was observed in almond cultivars grafted onto almond/peach hybrid rootstocks (GF677 and Garnem), which might account for the presence of PaLV in this crop. To our knowledge, this is the first confirmed report of almond as a natural PaLV host. The finding of PaLV in trees that did not show almond foamy canker symptoms rules out its involvement in this syndrome of unknown etiology and further contributes to a growing list of reports of asymptomatic PaLV infections in Prunus. Additional studies are however needed to evaluate the biological and agronomical significance of these findings and unambiguously establish whether PaLV should be a cause of concern or not.